Viability of Lactobacillus rhamnosus GG in provitamin A cassava hydrolysate during fermentation, storage, in vitro and in vivo gastrointestinal conditions. (April 2021) - Oguntoye, Modupeola A.; Ezekiel, Olufunke O.; Oridupa, Olayinka A.
Abstract: The effect of alginate encapsulation on the viability of Lactobacillus rhamnosus GG in provitamin A cassava hydrolysate used as a carrier during processing, storage, in vitro and in vivo gastro-intestinal conditions was assessed. Several studies in the literature have reported the viability of probiotics in non-dairy food matrices such as fruits and vegetables. However, there is need for further studies exploring the maintenance of probiotics in other non-dairy options and to evaluate the resistance of probiotics during passage through the gastro-intestinal tract. Lactobacillus rhamnosus GG ( LGG ) cells were microencapsulated in alginate beads (using emulsion and extrusion techniques), characterized and inoculated into provitamin A cassava starch hydrolysate. The survival/viability rates of LGG in provitamin A hydrolysate during storage (4 °C, 90 days), also in gastric and intestinal conditions ( in vitro and in vivo ) were measured. Free LGG cells in provitamin A cassava hydrolysates decreased rapidly in viability within the first 30 days of storage whereas encapsulated cells showed a gradual but insignificant decrease in viability. LGG cells maintained viability above 5 Log CFU/mL in hydrolysates with free LGG, and above 7 Log CFU/g in hydrolysates with encapsulated LGG by the end of 60 days of storage. Encapsulated LGG had 77.4 and 8.5% survival after 120 min in simulated gastric and intestinal juices, respectively. Growth direction index expanded up to 1.66 for LGG but decreased below −0.05 for total aerobes and Enterobacteriaceae in faeces of rats administered hydrolysate with encapsulated or free LGG by day 30. Encapsulated LGG showed better resistance during transit through gastrointestinal conditions.